ANALISIS PENGARUH MARKETING MIX (Produk, Harga, Promosi dan Lokasi) TERHADAP KEPUASAN PELANGGAN PRODUK PT GARUDAFOOD PUTRA PUTRI JAYA (Studi Kasus Pada Resto & corner PT Garudafood Pati) - Yasmina Ainun Mardhia; Poniman Poniman; Suwardi Suwardi (JOBS (Jurnal Of Business Studies), 2016)
In globalization era, the food industry business in Indonesia is growing rapidly along with the government's attention to build a stronger national economy. Every company must give good quality and the best services in order to win the competition. Customer satisfaction is the main thing that must be considered in the competition.The purpose of this research is to determine the influence of the marketing mix i.e. product, price, promotion and place on customer satisfaction. The method use in this research is multiple linear regression, which tested by t-test, F-test and R2-test. The result of this research shows that product, price, promotion and place partially have a significant positive influence on customer satisfaction. Simultaneously, product, price, promotion and place have a significant positive influence on customer satisfaction with the significant value of 0.000 . The result of the data analysis also shows that Product (X1) is the most dominant variable influenced the customer satisfaction at Resto & Corner PT Garudafood with the value of 0.487 .Overall, product, price, promotion and place gave contribution to customer satisfaction of 63.4%. while 36.7% are influenced by other variables are not described in this study.